Power losses analysis of multiphase DC-DC buck converter using OrCAD PSpice software - Ahmad Faiz Abdul Ghani; Mhd Hazwaj Poad; Afarulrazi Abu Bakar; Siti Nuraini Norazman; Mohd Azlee Noor Amran (Bulletin of Electrical Engineering and Informatics, 2022)
DC-DC buck converters have wide applications in portable electronic devices, battery chargers, and telecommunications. However, single-phase DC-DC buck converters have some drawbacks, especially in high current applications, where the increase in the size of the inductor will increase power losses, which significantly affects the overall efficiency of the converter. The multiphase configuration offers several advantages, such as reduction in output voltage ripple, input current ripple, conduction loss, and the physical size of the hardware. This paper presents an analysis of the power losses of the multiphase DC-DC buck converter with output power ranging between 50 watts to 250 watts. To verify the effectiveness of the multiphase converter, performance analysis was done using OrCAD PSpice software, where the number of phases was limited to five phases. This paper focused on power losses in the converter, namely conduction losses in diodes and MOSFETs, switching loss in MOSFETs, as well as losses in the inductor and capacitor. The relationship between the number of phases and factors of switching frequency, output, and the components’ internal resistance was also highlighted and discussed in detail.